STUDI PELACAKAN LULUSAN PROGRAM STUDI D3 TEKNIK SIPIL UNIVERSITAS NEGERI JAKARTA - Andri Aprianto; Arris Maulana; Nira Nasution (LPPM Universitas Negeri Jakarta, 2015)
This study aims to gain an overview and knowledge of the graduates of job profilesthat include the type of work that occupied areas, the waiting period to get a job, how to get a job, the amount of earned income, and employment status. The research was conducted on D3 in Civil Engineering who graduated in odd semester of 2005/2006 until the second semester 2009/2010. Sampling was done by purposive sampling. The study population numbered 113 people. The research sample consists of 29 people. This research uses descriptive method with the waythe survey. From the results of this study found that graduates who pursue work in the field of civilengineering work is now 82,76 %, while those working outside the field of civil engineering as much as 17,24 %. And for the first time job as much as 79,31 %worked in the field of civil engineering, while 20,69 % outside of civil engineering.Employment status of graduates on the job is now 55% is fixed and for the work of the first 72,41 % of the contract. Large salary in first job 48,28 % range between Rp 1.500.000 - Rp 2.500.000 per month, and the work that is now 27.58 % ranges between Rp 1.500.000 - Rp 2.500.000 and Rp 3.500.000 - Rp 4.500.000 per month. Graduation GPA of the most sought after companies ranging from 2,51-3,00. Organizational experience during campus 77.78 % were helped in the work world 48.27% obtained employment information from the internet. The waiting period to get a job at 86.21% is less than 3 months. The conclusion from this study that the quality of the D3 in Civil Engineering work has begun to be recognized in the world. From the field of employment, graduates can work not only on earth but also can ketekniksipilan outside of civil engineering.Although most of the graduates are working in the world of civil engineering. And the expected results of this research can provide input to the future for D3 in Civil Engineering courses to be able to better tailor its curriculum current with the times to produce future graduates more competitive in the world of work.